796 THE IMPORTANCE OF CHEST X RAYS AS AN INITIAL INVESTIGATION IN ROUTINE ACUTE ELDERLY CARE ADMISSIONS. (8th March 2022) - Tantoush, M; Menon, V; Ahmed, N
Abstract: Introduction: The Chest X-Ray (CXR) is a common and central initial investigation for any patient that has been admitted via Accident and Emergency (A&E). In the context of elderly care, it is a useful measure of a patient's baseline functional status as well as a tool for cancer surveillance and other aspects of clinical care. Accurate documentation of CXR review is also imperative for closed loop communication of clinical information amongst a multi-disciplinary team. Methods: Twenty-eight random inpatients in a local NHS Trust Healthcare of Older People (HCOP) department were selected to be part of this two-cycle study. Using hospital database records, the CARESTREAM imaging system and patient clinical documentation, data including the following was collected: whether a CXR was completed, was CXR review documented in patient notes and initial reason for admission. As per local practice, all acute HCOP admissions should undergo a CXR and have an image review clearly documented in patients' clinical noting. The established target was 95% compliance for both. Following intervention by way of ward poaters and presentation at a local quality improvement meeting the cycle was repeated to ascertain improvement in compliance. Results: 22 (79%) HCOP patients had a CXR on admission. Of those completed CXRs, only 6 (27%) of these showed evidence of review (documentation in clinical noting). Following the above mentioned interventions, 25 (89%) of HCOP patients had a CXR on admission, showing an improvement. Of those completed CXRs, 20 (80%) showed evidence of documented clinical review– once again showing improvement. Conclusions: CXRs and their accurate documentation is an important aspect of the holistic care of the HCOP patient. Ensuring that compliance for completing the scan and documenting results should be a priority in clinical quality and safety. Our interventions have shown an improvement in compliance and resulted in sustainable change.